Prediction of benefit from carotid endarterectomy in individual patients: a risk-modelling study. European Carotid Surgery Trialists' Collaborative Group. - Rothwell, P; Warlow, C (1999)
BACKGROUND: Carotid endarterectomy lowers the risk of carotid territory ipsilateral ischaemic stroke, and is the treatment of choice, in patients with recently symptomatic 70-99% carotid stenosis. However, the 3-year risk of stroke on medical treatment alone is only about 20%. We investigated whether the efficacy of endarterectomy would be improved if patients with a high risk of stroke on medical treatment and a low risk of operative stroke or death could be identified. METHODS: We developed two prognostic models from data on patients with 0-69% carotid stenosis in the European Carotid Surgery Trial (ECST). The medical model predicted risk of ipsilateral carotid territory major ischaemic stroke (fatal or lasting longer than 7 days) on medical treatment and the surgical model predicted risk of major stroke and death within 30 days of endarterectomy. From these models we developed a prognostic score to identify patients with a high risk of stroke on medical treatment but a low operative risk. We validated the models and tested the scoring system on 990 ECST patients with 70-99% carotid stenosis assigned surgery (594) or medical treatment only (396). FINDINGS: When patients with 70-99% stenosis were stratified by the scoring system, which was based on seven independent prognostic factors, endarterectomy was beneficial in only 162 (16%) patients. The 5-year absolute risk of carotid territory ipsilateral major ischaemic stroke, operative major stroke, or death was lowered by 33% in the 16% of patients with a score of 4 or more (odds ratio 0.12 [95% CI 0.05-0.29], p<0.0001), but not in the other 828 (84%) patients (1.00 [0.65-1.54], p=0.7). INTERPRETATION: Many patients with recently symptomatic 70-99% carotid stenosis may not benefit from carotid endarterectomy. Validation of the predictive score is needed on external datasets, but risk-factor modelling could be useful to identify those patients in whom endarterectomy will be beneficial.